2012
DOI: 10.3892/or.2012.2153
|View full text |Cite
|
Sign up to set email alerts
|

Instability of mRNA expression signatures of drug transporters in chronic myeloid leukemia patients resistant to imatinib

Abstract: Despite the success of imatinib mesylate (IM) in the treatment of chronic myeloid leukemia (CML), approximately 30% of patients are resistant to therapy, mostly due to unknown causes. To profile the expression signatures of drug transporters throughout IM therapy and correlate them with resistance, we quantified mRNA expression levels of the SLC22A12, ABCB1, ABCC1, ABCG2 and MVP genes in consecutive samples from peripheral blood or bone marrow of CML … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 56 publications
(68 reference statements)
1
14
0
Order By: Relevance
“…However, as acquired CDR is a time-dependent process, the assessment of the mechanisms that are activated as cells to develop resistance is critical. One interesting phenomenon that we were able to identify in a model of chronic myeloid leukemia was the sequential activation of different ABC transporter expressions (ABCB1, ABCG2, ABCC1), as cells gained resistance to the tyrosine kinase inhibitor Imatinib [9], and the relatively unstable pattern of expression of these transporters in human samples [28]. These observations indicated that the time-dependent analysis of CDR is critical to a better understanding of the mechanisms involved.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, as acquired CDR is a time-dependent process, the assessment of the mechanisms that are activated as cells to develop resistance is critical. One interesting phenomenon that we were able to identify in a model of chronic myeloid leukemia was the sequential activation of different ABC transporter expressions (ABCB1, ABCG2, ABCC1), as cells gained resistance to the tyrosine kinase inhibitor Imatinib [9], and the relatively unstable pattern of expression of these transporters in human samples [28]. These observations indicated that the time-dependent analysis of CDR is critical to a better understanding of the mechanisms involved.…”
Section: Discussionmentioning
confidence: 91%
“…Several groups have developed cell lines resistant to specific cancer drugs, such as doxorubicin, or paclitaxel, to study biomarkers of CDR [25,26]. However, the time course of occurrence of resistance mechanisms has not always been possible to assess and is not yet generally known and understood [9,27,28]. Furthermore, another issue that has not been addressed is the mechanism underlying the loss of resistance to therapy once the challenge to these cells is withdrawn.…”
Section: Introductionmentioning
confidence: 99%
“…Major molecular response (MMR, i.e., ≤0.1% BCR-ABL1 IS ; IS – International Scale) is frequently observed during imatinib treatment regardless of the daily dose in patients with increased SLC22A1 (OCT1) activity. Patients with normal or reduced activity of this transporter benefit from an increase in the imatinib dose and achieve MMR more frequently than patients who received standard doses [9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…However, a further study in a smaller cohort of 33 patients showed no correlation between this polymorphic variant and response to treatment. 60 All studies involving the R61C variant showed no correlation between its occurrence in patients and response to imatinib. [61][62][63][64] Otherwise, patients carrying the G401S variant showed high probability of achieving major molecular response to the drug.…”
Section: Drugs and Pharmacogenomicsmentioning
confidence: 99%